STUDI AKTIVITAS NELAYAN KETURUNAN BUGIS-MAKASSAR WILAYAH PESISIR LAMPU SATU DI KOTA MERAUKE - Rosa Delima Pangaribuan; Imelda Carolina La Ode (AGRICOLA, 2017)
Fishing potensial in Merauke region increased by the number of household due to fishing dan trade activities as many as 2.040 trade fishing household (Rumah Tangga Usaha Penangkapan Ikan/ RTUPI) on sea water and 2.705 RTUPI on general aquatic area. Fishing activites of Bugis – Makassar fisherman is affected by season. Best season for fishing is on May until July. They were satisfied by the outcome of fishing in Merauke region which is showed in level of satifcation on this research.